An Overview of Artificial General Intelligence into Human Resources Management - Airyq, Irnin (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This paper aims to fill that gap by providing a complete review of how artificial general intelligence (AGI) might transform human resource management practices, building on existing AI applications and extending them to more complex and cognitively demanding activities. These are addressed both theoretical and practical contributions by reviewing the current research and exploring upcoming trends, highlighting AGI’s dual impact—its potential to improve efficiency while creating ethical, social, and operational issues. The data collection are selected through a wide range of peer-reviewed articles and conference papers from reputable databases between 2018 – 2024. AGI could cause significant alterations in labor dynamics, such as position redefinition, increased emphasis on data governance, and ethical decision-making in HR procedures. These are emphasized the significance of balancing innovation with human-centered approaches in HRM as AGI technologies advance. Finally, this study hopes to serve as a basis for future research, promoting greater discovery of AGIs